Understanding the relationships between commercial linefishing and Marine Protected Area governance in KwaZulu-Natal, South Africa - Munting, Enya Melissa (Rhodes University, 2026)
A social-ecological systems (SES) approach, viewing humanity as a component of natural systems, has been widely recognised as necessary for conservation, especially considering the prevalence of wicked problems in this discipline. Despite a supportive policy and research environment, this approach has not yet been implemented in South African Marine Protected Area (MPA) management. The MPAs in KwaZulu-Natal (KZN) share goals to facilitate linefish stock recovery, the sustainable use of linefish resources and, often, to protect cultural heritage. The offshore commercial linefishing sector (CLS) is a small commercial sector that uses traditional methods (linefishing with rod and reel) to catch fish off small boats (<10m). It is considered the oldest fishing sector in the country and supports many livelihoods. Commercial linefishers are generally experienced fishers, with documented expertise in their field. This study aims to contribute knowledge on the relationship between the CLS and MPAs associated with the fishery in KZN, which can be used in a SES management baseline for long-term MPA monitoring. To do this, an interdisciplinary, mixed methods approach was taken, drawing on ecological and social science approaches. For the ecological component, the population structure of 26 commercially important linefish species (chosen with input from fishers) was analysed using Baited Remote Underwater Stereo-Video sampling methods (n=271 deployments), comparing mesophotic reefs inside three MPAs (Pondoland, uThukela and iSimangaliso) with fished areas outside, and comparing management strategies within MPAs, using Generalised Additive Mixed Models. The social component is based on interviews with 21 commercial linefishing rights-holders in KZN to understand their perceptions of MPAs, including their governance, management and social-ecological impacts. Results indicate that from an ecological perspective, MPAs, especially No-Take Areas, effectively protect linefish species and contribute to improved population dynamics. From a social perspective, interviews found that: 1. Fishers believe that MPAs are effective and necessary for fisheries sustainability; 2. Monitoring and enforcement of fisheries and MPA regulations are poor and must be improved; 3. A poor relationship between fisheries managers, MPA managers, and commercial linefishers hinders the effectiveness of MPAs; and 4. A lack of diverse sources of information leads to misguided decision-making and long-term unsustainability of MPAs and fishery management. Together, these results show that the governance and management processes relating to MPAs (and fisheries more broadly) need to be revisited to enable integrated, holistic management of the SES. The final chapter explores a potential change pathway to action this goal by building a Theory of Change focusing on improving relationships among and between people and the ecological system, with communication and societal engagement with MPA management as key points of focus.
Keywords: Uncatalogued